2007
DOI: 10.5194/acp-7-55-2007
|View full text |Cite
|
Sign up to set email alerts
|

PM measurement campaign HOVERT in the Greater Berlin area: model evaluation with chemically specified particulate matter observations for a one year period

Abstract: Abstract. The HOVERT (HOrizontal and VERtical Transport of ozone and particulate matter) campaign held in the Berlin Brandenburg area in Eastern Germany from September 2001 to September 2002 allowed to collect a unique data set of the aerosol chemical speciation (daily averages) at traffic, urban and rural sites. These observations are used for a thorough evaluation of the aerosol part in the REM-CALGRID model (RCG) developed at the Free University of Berlin (FUB). For inorganic ions (sulphate, nitrate and amm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In this study, the highest sulphate concentrations were observed during the wintertime campaign; the mean concentration at University Campus Poorer performance for sulphate episodes in wintertime compared to summertime has been documented in other studies (e.g. Beekmann et al, 2007;Schaap et al, 2011;Pay et al, 2011), and may in part be due to difficulties in the meteorological simulation of these winter-time pollution episodes as well as issues of oxidant availability.…”
Section: Pm 25 Sulphatesupporting
confidence: 57%
See 1 more Smart Citation
“…In this study, the highest sulphate concentrations were observed during the wintertime campaign; the mean concentration at University Campus Poorer performance for sulphate episodes in wintertime compared to summertime has been documented in other studies (e.g. Beekmann et al, 2007;Schaap et al, 2011;Pay et al, 2011), and may in part be due to difficulties in the meteorological simulation of these winter-time pollution episodes as well as issues of oxidant availability.…”
Section: Pm 25 Sulphatesupporting
confidence: 57%
“…Baker and Scheff, 2007;Tesche et al, 2006;Gaydos et al, 2007;Mathur et al, 2008) using large scale measurement networks for their evaluation. There have been various modelling studies in Europe including comparisons with measured speciated aerosol such as Lazaridis et al (2005), Beekmann et al (2007), Chemel et al (2010), Renner and Wolke (2010), Lonati et al (2010), Andreani-Aksoyoglu et al (2011), Schaap et al (2011), Basart et al (2012) and Pay et al (2011). The modelling performance reported depends on component, season and location but the majority of these studies have reported an underestimation of observed concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The Eulerian grid model REM-Calgrid (RCG) simulates air pollution concentrations solving the advection-diffusion equation on a regular latitude-longitude-grid with variable resolution over Europe (Beekmann et al, 2007;Stern, 2006). RCG is offline-coupled to the German Weather Service operational NWP model COSMO-EU (Schättler et al, 2008).…”
Section: Model Description and Set-upmentioning
confidence: 99%
“…The EC fraction of the PM2.5 emissions for the different SNAP sectors were taken from [19]. For the OC fraction, the method proposed by [20] is applied as follows: an average OC/EC emission ratio of two was used for all sectors, i.e. the OC fraction were set as twice the EC fractions, except if the sum of the two fractions exceed the unity.…”
Section: Emission Datamentioning
confidence: 99%